Is hormonal contraceptive risk for congenital malformation? - Hiremath, Prabhuswami; Patange, R. P.; Salunkhe, J. A.; Mohite, Vaishali R.; Naregal, Prakash (International Journal Of Community Medicine And Public Health, 2019)
Background: Little research is conducted in the safety of emergency contraceptives so the potential for developmental toxicity has not been evaluated. Methods: This hospital based descriptive study was conducted at tertiary care center, Krishna Hospital. Mothers who are diagnosed to have congenital birth defected fetus through antenatal examinations, delivered baby with diagnoses of congenital malformation, congenital malformed admitted neonates at Tertiary care hospital or came for reference services were assessed from September 2016 to August 2017. Results: The prevalence with number of birth, it is 1.4% and calculating with number of neonates admitted its prevalence rate is 5.3%. Overall in the hospital the prevalence noted is 0.2%. 283 mothers were diagnosed to have congenital malformation baby, among these, 264 (93.3%) mothers not had any history of birth control pills use and only 19 (6.7%) mothers stated that they used the birth control pills. Those used birth control pills in those 4 babies (1.4%) born with nervous system defects, 3 babies (1.1%) had cleft lip and cleft palate, and 2 (0.7%) babies had digestive system, musculoskeletal system and chromosomal abnormalities. Association between congenital malformation and history of Use of birth control pills shows strong association. Conclusions: The problem of conclusively proving a small increase in the incidence of rare abnormalities is very formidable. This may be due in part to the fact that the anomalies associated with hormonal contraceptives may occur primarily in those children who are predisposed genetically.